2020
DOI: 10.18502/cmm.6.1.2505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of fungi causing colonization and infection in organ transplant recipients: a one-year prospective study

Abstract: Background and Purpose: Organ transplant recipients are vulnerable to fungal infections. The aim of this study was to determine the prevalence of fungal colonization and infections among patients who underwent various transplantations and molecularly characterize the etiological agents. Materials and Methods: This study was conducted on candidates for transplantation in Imam Khomeini Hospital, Tehran, Iran, from April 2017 to April 2018. All patients were monitored for fungal colonization or infections b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…( 21 ) Furthermore, previous studies’ results demonstrated that the prevalence of oral candidiasis in patients who have undergone solid organ transplants ranges from 15-34%. ( 22 - 25 ) This study found a higher prevalence of candidiasis than López-Pintor et al, ( 26 ) who reported candidiasis infection in 7.4% of patients who underwent kidney transplantation, indicating that the incidence of fungal infections is higher in patients receiving liver transplantation. Notably, the frequency of oral and oropharyngeal candidiasis infections has increased dramatically in recent decades, mainly because of an increase in the number of patients with compromised immune systems.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…( 21 ) Furthermore, previous studies’ results demonstrated that the prevalence of oral candidiasis in patients who have undergone solid organ transplants ranges from 15-34%. ( 22 - 25 ) This study found a higher prevalence of candidiasis than López-Pintor et al, ( 26 ) who reported candidiasis infection in 7.4% of patients who underwent kidney transplantation, indicating that the incidence of fungal infections is higher in patients receiving liver transplantation. Notably, the frequency of oral and oropharyngeal candidiasis infections has increased dramatically in recent decades, mainly because of an increase in the number of patients with compromised immune systems.…”
Section: Discussionmentioning
confidence: 47%
“…Notably, the frequency of oral and oropharyngeal candidiasis infections has increased dramatically in recent decades, mainly because of an increase in the number of patients with compromised immune systems. ( 25 )…”
Section: Discussionmentioning
confidence: 99%
“…A distinct situation is the case of airborne microorganisms, such as filamentous fungi (Aspergillus, Rhizopus, Mucor, etc.) and other already mentioned environmental pathogens (H. capsulatum, C. neoformans) colonizing the host via the upper respiratory tract [14,16,17].…”
Section: Opportunistic Infections and Coinfectionmentioning
confidence: 99%
“…Aspergillosis usually occurs after manifestation of pulmonary disease in immunocompromised and organ transplant patients [17]. Aspergilli rarely cause fungaemia, with the exception of Fusarium spp.…”
Section: The Aetiological Agents: Ntm and Fungimentioning
confidence: 99%
See 1 more Smart Citation